A study of Community Based Nutritional Intervention and prevention of malnutrition - Toppo, Neelam Anupama (Indian Journal of Community Health, 2015)
Background: PEM is one of the major health and nutritional problem in India. It is not only an important cause of childhood mortality and morbidity but also leads to permanent impairment of both physical and mental growth of those who survive. Malnutrition is implicated in >50% of deaths of <5 children (5 million/yr). Improving nutrition for children is crucial in meeting two of the Millennium Development Goals. According to national family health survey-3 there is considerable variation across states with Madhya Pradesh recording the highest rate for underweight children (60.3%) and Kerala among the lowest (28.8%). The great majority of cases of PEM nearly 80% are intermediate that is mild and moderate cases which frequently go unrecognized. These are the fact that made us to pick this issue in order to benefit the children of locality to some extent. Objectives: To identify under 5 year children with malnutrition, To demonstrate the method of preparing high protein mix diet and to educate mothers about adequate recommended diet as per age of children, To find out whether high protein mix improves nutritional status of identified malnourished children. Methodology: It was cross sectional and interventional study carried out in two villages of Jabalpur districts during the period of three months among 100 under five children. We had screened them and calculated weight for age (%) and categorized them according to Gomez Classification that is normal, mild, moderate and severe malnutrition. Intervention was done on malnourished children then 4 follow ups at the interval of 15 days. Intervention strategies: Nutrition education and provision of High Protein Mix Diet. Result: 12% children were identified as malnourished where 7% were having mild grade malnutrition and 5% with moderate grade of malnutrition. Among male there were 14.04% children were malnourished while among female 9.3% were malnourished. After intervention 50% children were showing change in the grade where one shifted to normal grade and 4 to mild grade. Weight of malnourished children steadily increasing during follow-up. Conclusion: Regular and proper age wise dietary intake and High protein mix diet can significantly contribute to correct malnutrition at community level.